NFT (token no fungibles) y sus implicaciones en el mercado de valores - Gámez Baracaldo, María Camila (2023)
The impact generated by the accelerated development of NFT’s creates a series of risks and legal problems, among which the legal, the impact on intellectual property, the protection of the purchasers of this type of tokens, fraud prevention and the possible impact of NFT’s on financial markets are the most important. The purpose of this document is to analyze whether the regulatory framework of the securities market is applicable to NFT’s based on the following assumptions: i) NFT’s, understood individually as a digital representation, cannot be considered as securities; ii) in States where the definition of securities includes the concept of “investment contract”, NFT’s could be considered as securities, as long as they meet the requirements of the Howey Test; iii) in States where there is no definition of investment contracts, NFT’s could be considered as securities, provided that they meet the requirements for such purpose—the existence of a negotiable right, issued in mass or in series within a public offering of securities, and that its purpose is to obtain resources from the public by way of investment—; and iv) that the recognition of NFT’s as securities would lead to the application of regulatory frameworks of the capital market in matters such as registration before the financial authorities, provision of information and investor protection schemes. This text will describe the origin and current scenario of NFT’s. Likewise, the different positions of supervisory and regulatory authorities at a global level will be analyzed with respect to these tokens; and, finally, some reflections will be made from the point of view of securities market regulation with respect to the aforementioned non-fungible tokens.